(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
Using the “Bioscope” hardware complex, it was shown that an oxygen deficiency leads to certain changes in the statistical parameters of the integrative state of animals both during and after hypoxia exposure. However, after 10 days of using horseradish roots (Armoracia rusticana) as an antihypoxic food supplement, in contrast to the control, significant changes in the recorded signal are observed both during and after hypoxic exposure. These changes indicate the facilitating effect of horseradish roots in conditions of oxygen deficiency.